The Use of Code-Switching and Code-Mixing to Express Social Identity in The Novel How The Garcia Girls Lost Their Accents by Julia Alvarez - Nurlita Dhaffa Romansyah; Muhammad Adam (Prologue: Journal on Language and Literature, 2023)
This research analyzed code-switching and code-mixing to express social identity in the novel How The Garcia Girls Lost Their Accents by Julia Alvarez. The studies aim to find the types of code-switching and code-mixing and how it is used to express the social identity in the novel. The theory that used in this research is the code-switching and code-mixing theory by Suzanne Romaine and the social identity theory by John J. Gumperz to find the data used to express social identity in the novel. The source of data was collected from the character’s quotations and narrations of the story in the novel. The result of this research, based on the theory used, the researcher found that the intra-sentential type of CS and CM are frequently used for 23% to express the social identity gender in the novel, followed by the other types of CS and CM in another expression of social identity. The social identity gender shown in the novel for CS and CM are most use by the women character for expressing their social identity, as the story is have more women characters than the opposite gender.